(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Big data Analytics is a blend of immense and compound data sets that have the enormous capacity of data, social media analytics, data management competence, real-time data. Big data analytics is the process of learning gigantic quantities of data. To examine this vast volume of data Apache Hadoop can be used. Hadoop is an open-source package that allows the distributed processing of hefty data sets across clusters of service servers. It is intended to scale up from a solitary server to thousands of apparatuses, with a actual high degree of fault lenience.